2015
DOI: 10.1073/pnas.1421803112
|View full text |Cite
|
Sign up to set email alerts
|

Allelic polymorphism of GIGANTEA is responsible for naturally occurring variation in circadian period in Brassica rapa

Abstract: GIGANTEA (GI) was originally identified by a late-flowering mutant in Arabidopsis, but subsequently has been shown to act in circadian period determination, light inhibition of hypocotyl elongation, and responses to multiple abiotic stresses, including tolerance to high salt and cold (freezing) temperature. Genetic mapping and analysis of families of heterogeneous inbred lines showed that natural variation in GI is responsible for a major quantitative trait locus in circadian period in Brassica rapa. We confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 55 publications
(60 reference statements)
2
50
2
Order By: Relevance
“…As a positive control, we showed that a loss-of-function gi-1 mutant obtained by TILLING in B. rapa R-o-18 increased salt tolerance, as determined by photosynthetic efficiency (Fv/Fm) (Fig. 6b), consistent with the results of Xie et al (2015). In response to salt stress, fresh weight and photosynthetic efficiency (Fv/Fm) were significantly greater in the GK1-11 and GK1-12 lines than in the DH03, GK4-4 and GK4-6 lines.…”
Section: Effect Of Reduced Gi Expression On Arabidopsis Plantssupporting
confidence: 86%
See 4 more Smart Citations
“…As a positive control, we showed that a loss-of-function gi-1 mutant obtained by TILLING in B. rapa R-o-18 increased salt tolerance, as determined by photosynthetic efficiency (Fv/Fm) (Fig. 6b), consistent with the results of Xie et al (2015). In response to salt stress, fresh weight and photosynthetic efficiency (Fv/Fm) were significantly greater in the GK1-11 and GK1-12 lines than in the DH03, GK4-4 and GK4-6 lines.…”
Section: Effect Of Reduced Gi Expression On Arabidopsis Plantssupporting
confidence: 86%
“…These oscillation patterns are similar to those of GI expression in Arabidopsis (Fowler et al 1999;Park et al 1999) and Brachypodium distachyon (Hong et al 2010), which peaked at ZT12 and ZT8 under LD and SD conditions, respectively. This pattern was also similar to that of BrGI transcripts in the R500 and IMB211 B. rapa accessions, which peaked at ZT8 under a 12/12 h photoperiod (Xie et al 2015). To determine if the rhythmic cycling of the BrGI transcript was under the control of the circadian clock, B. rapa plants entrained under either LD or SD conditions were transferred to continuous light conditions.…”
Section: Circadian Clock Regulation Of Brgi Expressionmentioning
confidence: 52%
See 3 more Smart Citations